(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
X-Ray Image Intensifier (XRII) suffers from serve distortion in C-arm CT imaging system. To overcome the challenging problem, this paper proposes a novel XRII correction based on the Biharmonic Spline Surface Interpolation (BSSI) framework. In our study, two functions X_2 =f(X_1, Y_1) and Y_2 =f(X_1, Y_1) are first developed to map the relation between pixels positions in the distorted XRII image and reference image. A bilinear interpolation can then be applied to estimate the corrected pixel intensities to achieve the final image. The proposed approach can well overcome the discontinuities problems in local algorithms and achieve improved accuracy in distortion correction. Experiment results demonstrate that the proposed algorithm is capable of providing XRII images with higher correction precision than classical algorithms.